Actinidia arguta (Sieb. et Zucc.) Planch. ex Miq.: A Review of Phytochemistry and Pharmacology - Zhang, Haifeng; Teng, Kun; Zang, Hao (Molecules (Basel, Switzerland), 2023)
Actinidia arguta (Siebold & Zucc.) Planch ex Miq. (A. arguta) is a highly valued vine plant belonging to the Actinidia lindl genus. It is extensively utilized for its edible and medicinal properties. The various parts of A. arguta serve diverse purposes. The fruit is rich in vitamins, amino acids, and vitamin C, making it a nutritious and flavorful raw material for producing jam, canned food, and wine. The flowers yield volatile oils suitable for essential oil extraction. The leaves contain phenolic compounds and can be used for tea production. Additionally, the roots, stems, and leaves of A. arguta possess significant medicinal value, as they contain a wide array of active ingredients that exert multiple pharmacological and therapeutic effects. These effects include quenching thirst, relieving heat, stopping bleeding, promoting blood circulation, reducing swelling, dispelling wind, and alleviating dampness. Comprehensive information on A. arguta was collected from scientific databases covering the period from 1970 to 2023. The databases used for this review included Web of Science, PubMed, ProQuest, and CNKI. The objective of this review was to provide a detailed explanation of A. arguta from multiple perspectives, such as phytochemistry and pharmacological effects. By doing so, it aimed to establish a solid foundation and propose new research ideas for further exploration of the plant’s potential applications and industrial development. To date, a total of 539 compounds have been isolated and identified from A. arguta. These compounds include terpenoids, flavonoids, phenolics, phenylpropanoids, lignin, organic acids, volatile components, alkanes, coumarins, anthraquinones, alkaloids, polysaccharides, and inorganic elements. Flavonoids, phenolics, alkaloids, and polysaccharides are the key bioactive constituents of A. arguta. Moreover, phenolics and flavonoids in A. arguta exhibit remarkable antioxidant, anti-inflammatory, and anti-tumor properties. Additionally, they show promising potential in improving glucose metabolism, combating aging, reducing fatigue, and regulating the immune system. While some fundamental studies on A. arguta have been conducted, further research is necessary to enhance our understanding of its mechanism of action, quality evaluation, and compatibility mechanisms. A more comprehensive investigation is highly warranted to explore the mechanism of action and expand the range of drug resources associated with A. arguta. This will contribute to the current hot topics of anti-aging and anti-tumor drug research and development, thereby promoting its further development and utilization.